2012
DOI: 10.3174/ajnr.a3306
|View full text |Cite
|
Sign up to set email alerts
|

Screening Cervical Spine CT in the Emergency Department, Phase 2: A Prospective Assessment of Use

Abstract: BACKGROUND AND PURPOSE:The National Emergency X-Radiography Utilization Study Low-Risk Criteria were established to identify patients with a low probability of cervical spine injury in whom imaging of the cervical spine was unnecessary. The purpose of this study was to ascertain the number of unnecessary cervical spine CT studies on the basis of proper application of established clinical guidelines and, secondarily, to determine indications for ordering studies in the absence of guideline criteria.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 11 publications
(24 reference statements)
0
15
0
Order By: Relevance
“…However, in a substantial amount of patients (56%) not the recommended number of radiographs was performed. The adherence to the guideline when to obtain radiographic imaging in paediatric trauma patients in this study was better than the adherence of the NEXUS criteria and the CCR in the adult population varying from 4 to 38% [16][17][18][19].…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…However, in a substantial amount of patients (56%) not the recommended number of radiographs was performed. The adherence to the guideline when to obtain radiographic imaging in paediatric trauma patients in this study was better than the adherence of the NEXUS criteria and the CCR in the adult population varying from 4 to 38% [16][17][18][19].…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies showed that adherence to the NEXUS criteria and CCR in adults varies widely [16][17][18][19]. However, there are no studies that describe the adherence to the cervical spine clearance protocol in children.…”
Section: Introductionmentioning
confidence: 99%
“…Since their inception, a few studies have directly compared the CCR and NEXUS criteria and have found the CCR to slightly outperform NEXUS in selecting patients at risk for cervical spine injury [6,7]. However, multiple studies have validated the sensitivity of both the NEXUS and CCR criteria for identifying clinically significant cervical spine injuries [7][8][9][10][11][12]. The ACR does not take a position on the relative merits of the two sets of criteria; however, the ACR recognizes both are in widespread clinical practice and produce concordant predictions for most patients.…”
Section: Summary Of Literature Review Introduction/backgroundmentioning
confidence: 99%
“…It is unknown what the appropriate or acceptable rate of scanning is, and the present study may serve as a reference point for future studies. Two prospective studies found that strict application of NEXUS criteria before cervical spine imaging would result in a 16–20% reduction in cervical spine CT with negative findings, and abbreviated Canadian C‐spine criteria in a 28.9% reduction . The sample size is too small to draw conclusions as to over utilisation of CT imaging; however, a 1.1% fracture yield (95% CI 0.2–4.5; 2/176) seems very modest, and strategies to decrease unnecessary scanning may be considered.…”
Section: Discussionmentioning
confidence: 99%